(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to show the possibility of adopting the market approach to measure the fair value of biological assets in Iraq, by applying to a sample of the company listed on the Iraq Stock Exchange, where the Middle East Fish Production and Marketing Company was selected from among 7 companies representing the agricultural sector in Iraq, and according to the availability of data and for five years, the financial statements were presented of the measurement and disclosure of biological assets at fair value according to the market approach, One of the most important conclusions reached by the researcher is the The possibility of measuring and disclosing biological assets at fair value according to the market approach in the Iraqi agricultural economic units based on the data of the Central Bureau of Statistics, while the most prominent recommendations reached by the researcher were the development of methods of measuring fair value in the Iraqi market and the adoption of the market approach as it suits the Iraqi environment.